Exogenic glucose as an electron donor for algal hydrogenases to promote hydrogen photoproduction by Chlorella pyrenoidosa. (October 2019) - Liu, Jun-Zhi; Ge, Ya-Ming; Sun, Jing-Ya; Chen, Paul; Addy, Min; Huo, Shu-Hao; Li, Kun; Cheng, Peng-Fei; Ruan, Roger
Highlights: Algal hydrogen photoproduction was almost doubled by glucose addition. Positive correlation between H2 yield and glucose consumption was observed. Deuterated glucose was used to distinguish if glucose served as a proton donor. Proposed a tentative electron transport route from glucose to algal hydrogenase. Abstract: In this work, glucose addition (0.7 g l −1 ) almost doubled hydrogen yield of Chlorella pyrenoidosa (121.1 ml l −1 vs 65.5 ml l −1 ), with a positive correlation between hydrogen production and glucose consumption (−0.977, P < 0.01). When the electrons transport from water photolysis to algal hydrogenase was inhibited, the hydrogen productivity declined by 21.1%; whereas it dramatically decreased by 70.9% when the algal nicotinamide adeninedinucleotide dehydrogenase (NADH) was inhibited. Therefore, in the presence of glucose, the electrons for algae based hydrogen production would be mainly from glucose glycolysis rather than water photolysis. Further deuterated-glucose trial indicated that the glucose might serve as an electron donor for algal hydrogenases. Finally, a tentative electron transport route from glucose to algal hydrogenase was proposed, hoping to provide more scientific direction for further algae-based hydrogen production improvement.